2013
DOI: 10.1039/c2ce26578h
|View full text |Cite
|
Sign up to set email alerts
|

In-situ synchrotron SAXS and WAXS investigations on deformation and α–β transformation of uniaxial stretched poly(vinylidene fluoride)

Abstract: In-situ synchrotron SAXS and WAXS investigations on deformation and a-b transformation of uniaxial stretched poly(vinylidene fluoride)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 60 publications
4
51
0
Order By: Relevance
“…Indeed using in situ synchrotron radiation X‐ray scattering techniques provides rich structure–property information for many semicrystalline polymers . Our previous works have endorsed the effectiveness and accuracy of synchrotron radiation techniques. In this article, by means of synchrotron radiation WAXS and SAXS, which are ideal analysis techniques to probe changes (1–1,000 Å) in structure, we found that the structure evolution above T g is quite different from that below T g .…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed using in situ synchrotron radiation X‐ray scattering techniques provides rich structure–property information for many semicrystalline polymers . Our previous works have endorsed the effectiveness and accuracy of synchrotron radiation techniques. In this article, by means of synchrotron radiation WAXS and SAXS, which are ideal analysis techniques to probe changes (1–1,000 Å) in structure, we found that the structure evolution above T g is quite different from that below T g .…”
Section: Introductionsupporting
confidence: 87%
“…This mechanism could weaken the increscent d ach evolution during deformation and then stalemate it. After a plateau stage, the quite stretched amorphous phase is at a disadvantage and the lamellar fragments are responsible for the fall of long spacing . The lamellar fragments arrange and diffuse in the amorphous phase that lead the SAXS scattering to present a structure with more lamellae and smaller long spacing.…”
Section: Resultsmentioning
confidence: 99%
“…The ultra-high intensity and brilliance dramatically enhance the time-resolution in real-time experiments with millisecond precision (Bilderback et al, 2005). Therefore, synchrotron radiation has become a powerful tool for probing subtle and complex structural changes in various sciences, such as chemistry, biology, physics, medicine and material science (Gonzalez et al, 2003;Guo et al, 2013;Nojima et al, 2014;Tafforeau et al, 2006). Noguchi et al (2014) employed synchrotron radiation to investigate the polymorphic transformation of clarithromycin form II crystals under acidic condition.…”
Section: Introductionmentioning
confidence: 99%
“…As for the influences of some key fabrication parameters, many previous works to date focused on the fabrication steps after initialization crystallization process (e.g., stretching and poling) [11,15,16]. Only a few works explored the influences of initial crystallization temperature on the phase structures of PVDF homopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the critical theme is to increase the fraction of β-phase in the polymer. To date, several traditional methods have been developed to improve the phase transformation from α-phase to β-phase, such as high pressure, stretching, poling, annealing, polymer blending [10,11,[13][14][15][16][17][18][19], etc. Among them, the most common and important one is the mechanical stretching in solution casting method.…”
Section: Introductionmentioning
confidence: 99%